Endovascular treatment for pelvic congestion syndrome associated with inferior vena cava anomaly. Issue 1 (March 2018) - Comai, Alessio; Dellis, Charalampos; Rielli, Emanuela; Bonatti, Giampietro
Introduction: Pelvic congestion syndrome is described as chronic pelvic pain arising from dilated and refluxing pelvic veins, although the causal relationship between pelvic vein incompetence and pelvic pain is not established. Embolization appears to provide symptomatic relief in the majority of women and is safe. Case report: We report the case of a young woman affected by pelvic congestion syndrome associated with a rare venous anomaly, duplicity of inferior vena cava with azygos vein continuation. Endovascular treatment consisted of detachable coil embolization of the right ovarian vein, as pelvic pain was prevalently on this side. Technical and clinical outcome were positive with a significant improvement of quality of life. Conclusion: This is the first reported case of a pelvic congestion syndrome associated with inferior vena cava anomaly and effectively treated with ovarian vein embolization.